Effects Of Concentrate And Mineral Supplementation On The Mineral Status And Performance Of A Beef Breeding Herd - Hew, Peng Yew (1985)
Two experiments were conducted in Pahang, Malaysia. In Experiment 1,175 Droughtmaster cows with nursing calves_ were randomly assigned to four treatments: (1) phosphorus wineral block (PMB) + salt + concentrate (conc.); (2) PMB + salt; (3) Dica1cium phosphate (DCP) + salt + conc.; and (4 ) salt + conc. In Experiment 2,193 cows were randomly assigned to four treatments: (1) Mineral meal (MM) + 0.68 kg conc.; (2) MM + .36 kg conc.; (3) salt only; and (4) MM only. Criteria for evaluation were P, Ca, Mg, K, Cu, Fe and Zn content of blood, forage ancl soil samples. Reproductive performance and body weight changes were also recorded. The trend for blood plasma minerals in Experiment 1 was a general decline initially followed by an increase towards the end of the trial for Ca, Mg and K. An increase in Fe and Cu was initially observed, followed by a decline. Zinc plasma levels declined throughout the experiment. The blood profile in Experiment 2 indicates deficiencies in plasma Mg, Fe and Cu. Soil pH values ranged from 5 .0 to 6.9 in Experiment 1 and 4.0 to 6.9 in Experiment 2. Soil extractable macroelements were adequate to meet the requirements of forages, except for P in both experiments. Macroelements in forages appear to be adequate, but some samples may be borderline for Cu and Zn in Experiment 1. Improvement in cattle productivity from mineral supplementation reflected mineral deficiencies in forages. Pregnancy rates were favourably affected by concentrate supplements in Experiment 1. Percentage calf crop and calf crop weaned were likewise affected. Birth weights and calf weaning weights were highest in Groups supplemented with minerals. Results from Experiment 2 suggests that concentrates did not enhance pregnancy rates, but calf crop was improved. Birth weights, percentage calf crop weaned and weaning weight were improved with mineral supplementation.